Nutritional Therapy for Burns in Children: A Mini-Review - Galfo, Myriam; Bellis, Andrea De; Melini, Francesca (Highlights on Medicine and Medical Research Vol. 9, 2021)
Burns are a serious injury and one of the leading causes of trauma in children, particularly in the first five years of life. Because of a marked hypermetabolism immediately or early after burn and protection from infections, nutritional support has been recognised as one of the most critical aspects of medical burns care in terms of mere nutrition for these patients. Resting energy expenditure (REE) has a curvilinear increasing trend according to the total burned surface area (TBSA), and indirect calorimetry is considered the most accurate method to evaluate the energy output of burned patients. Protein need in burned children is generally agreed to be higher than recommended dietary allowance and intake thereof should range around 1.5–3.0 g/kg/die. Carbohydrate intake should be 55–60% of total energy intake (TEI), whereas lipids should be lower than 35% of TEI. As regards micronutrients intake, children suffering from major burns should receive vitamin supplementation in the form of a multivitamin, in addition to vitamin C, vitamin A and zinc sulfate to ensure adequate wound healing. Enteral nutrition is the first line of nutritional care for a burned patient, and it should be started right away. To resolve patient hypermetabolism, a sufficient amount of calories must be given. It is also important to increase protein intake as long as wound healing is satisfactory. When enteral nutrition is contraindicated or not feasible, parenteral nutrition is used.